Capacity Building Skills for Teachers of Block/Bricks Laying and Concreting for Effective Teaching of Computer Aided Drafting in Technical Colleges in Rivers State - P.C. Okwelle; F.N. Ebikeseye (East Asian Journal of Multidisciplinary Research, 2022)
The study examined capacity building skills for teachers of block/bricks laying and concreting for effective teaching of Computer Aided Drafting (CAD) in government technical colleges in Rivers State. One research question was answered with one corresponding null hypothesiss that was formulated and tested at 0.05 significance level. The population of the study was 23 Block/Brick Laying and Concreting personnel comprising 16 teachers and 8 instructors from four technical colleges in Rivers State. There was no sampling due to small population size. The instrument for the data collection was a self-structured questionnaire designed after the pattern of Likert-5 point rating scale. The instrument was validated by two experts in the Department of Vocational and Technology Education in Rivers State University, Port Harcourt. The reliability of the instrument was established through test-retest method for different sections of the instrument. A reliability coefficients of 0.85 was established for the instrument. Research question was answered with Mean and Standard Deviation while hypothesis was tested using independent sample t-test. The study found that majority of the skills outlined in the study are needed by teachers of Block/Bricks Laying and Concreting for effective teaching of Computer Aided Drafting (CAD) in Government Technical Colleges in Rivers State. Based on the finding of the study, it was recommended that workshops and seminars should be organized by government for teachers of Bricks/Block Laying and Concreting on basic design process, drafting materials and equipment, working drawing, sketching and designing and computer aided drafting in order to build their capacity